Implementation of Merdeka Belajar Kampus Merdeka Program: Perception of Lecturers, Students, and Staff of the University - Tatang Ary Gumanti; Mira Sekar Arumi (AL-ISHLAH: Jurnal Pendidikan, 2023)
Implementing the Independent Campus-Freedom to Learn (MBKM) programme has significantly changed the learning process. It is mandatory for universities to implement the programme. Nevertheless, the programme encountered significant challenges in its execution due to the outbreak of COVID-19, rendering the optimal conditions for its deployment unattainable. Following a period of nearly two years of implementation, it is imperative for tertiary institutions to undertake an evaluation of the program's accomplishments. The outcomes of this evaluation are anticipated to serve as a foundation for future enhancements. This paper aims to examine the perspectives of students, instructors, and education professionals regarding the execution of the MBKM programme. The survey was administered to participants from three distinct groups, who provided justifications for a series of questions or assertions. The survey data underwent analysis using descriptive analytic techniques. In conjunction with the survey, this study incorporates further analysis through the utilisation of focus group discussions (FGDs) encompassing three distinct groups of participants, including structural officials. The findings indicated that the internship programme within the company emerged as the primary preference among students enrolled in the MBKM programme. A significant proportion of students believe that the MBKM programme does not delay their academic progression; as a result, they express their intention to participate in the programme and even advocate for its adoption among their peers. The level of comprehension among students, instructors, and education personnel regarding the MBKM programme is moderate. The findings derived from the analysis of the Focus Group Discussion (FGD) suggest that there is a requirement to enhance socialisation and improve the comprehensibility of course conversion.